Transcription Factor NFIB Is a Driver of Small Cell Lung Cancer Progression in Mice and Marks Metastatic Disease in Patients - Semenova, Ekaterina A. (Cell Press, 2016)
Small cell lung cancer (SCLC) is an aggressive neuroendocrine tumor, and no effective treatment is available to date. Mouse models of SCLC based on the inactivation of Rb1 and Trp53 show frequent amplifications of the Nfib and Mycl genes. Here, we report that, although overexpression of either transcription factor accelerates tumor growth, NFIB specifically promotes metastatic spread. High NFIB levels are associated with expansive growth of a poorly differentiated and almost exclusively E-cadherin (CDH1)-negative invasive tumor cell population. Consistent with the mouse data, we find that NFIB is overexpressed in almost all tested human metastatic high-grade neuroendocrine lung tumors, warranting further assessment of NFIB as a tumor progression marker in a clinical setting.